An emission surface approach for noise propagation from high speed sources - Vendemini, L.; Vigevano, L. (My University, 2017)
The computer graphics algorithm of the marching cubes is adopted to compute the emission surface corresponding to a permeable Ffowcs Williams-Hawkings surface moving at arbitrary speeds. The algorithm is capable to successfully reconstruct the multiple disjoint surfaces generated by a transonic or supersonic motion of the source. A preliminary validation of the method, carried out for a two-blade rotor with simplified aerodynamic models, has given encouraging results.